The subject of the crime provided for article 203-1 of the criminal code of Ukraine and its characteristics - Бартман, Ю. Д. (Problems of legality, 2014)
The article is devoted to the problem of determination characteristics of disks for laser reading systems, matrices, equipment and raw materials for their production as subjects of the crime provided for article 203-1 of the Criminal Code of Ukraine. The basic characteristics of the pointed subjects are analized in the research. Among additional characteristics the author underlines the specific features inherent only to particular subjects of this crime.